1996
DOI: 10.1128/cmr.9.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Detection of infection or infectious agents by use of cytologic and histologic stains

Abstract: A wide variety of stains are useful for detection of different organisms or, for viruses, the cytopathologic changes they induce, in smears prepared directly from clinical specimens and in tissue sections. Other types of stains, such as hematoxylin and eosin, are used routinely to stain tissue sections and are most valuable for assessing the immunologic response of the host to the invading pathogen. In many cases, the pattern of inflammation provides important clues to diagnosis and helps to guide the selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 174 publications
(168 reference statements)
0
70
1
3
Order By: Relevance
“…Although the cases of paracoccidioidomycosis and rhinosporidiosis showed only focal staining, infections caused by other organisms showed a very high (≥90%) percentage of organisms staining in at least some cases. Interestingly, although Sporothrix has been reported to be FMS positive [7,13], the one case of sporotrichosis in our study was negative.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Although the cases of paracoccidioidomycosis and rhinosporidiosis showed only focal staining, infections caused by other organisms showed a very high (≥90%) percentage of organisms staining in at least some cases. Interestingly, although Sporothrix has been reported to be FMS positive [7,13], the one case of sporotrichosis in our study was negative.…”
Section: Discussioncontrasting
confidence: 72%
“…It has been suggested that the stain is relatively specific for infections caused by Cryptococcus neoformans. In fact, this notion has become very prevalent in the peer-reviewed literature [3,[7][8][9][10][11][12][13] as well as textbooks [14][15][16][17]. The idea of a specific stain is appealing because the morphology of Cryptococcus can overlap with that of other organisms, especially when capsular stains (eg, mucicarmine) are negative.…”
Section: Introductionmentioning
confidence: 98%
“…However, to be sure we detected all organisms present, we did not use granulomas to performed a guided search for mycobacteria [24], because organisms in paucibacillary MAP disease of ruminants and tuberculoid leprosy of humans are not confined to granulomas [25e29]. Applying the threshold of 10 positive fields, nearly one-half of CD patients were negative, indicating either the absence of mycobacteria or a bacterial burden less than 10 bacilli per milligram of tissue [12].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi may also be detected in smears stained with special stains such as acridine orange, PAS stain, and Gomori methenamine silver. 21 Fungi, such as Candida and Aspergillus species, and the zygomyces (Mucor) can often be identified according to the morphological characteristics of their hyphae. Aspergillosis is an uncommon opportunistic fungal infection caused by a variety of species of which A fumigatus and A niger are the common ones.…”
Section: Discussionmentioning
confidence: 99%